2020
DOI: 10.21928/uhdjst.v4n1y2020.pp9-17
|View full text |Cite
|
Sign up to set email alerts
|

Thresholding-based White Blood Cells Segmentation from Microscopic Blood Images

Abstract: Digital image processing has a significant role in different research areas, including medical image processing, object detection, biometrics, information hiding, and image compression. Image segmentation, which is one of the most important steps in processing medical image, makes the objects inside images more meaningful. For example, from microscopic images, blood cancer can be identified which is known as leukemia; for this purpose at first, the white blood cells (WBCs) need to be segmented. This paper focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Zhana et al proposed a new algorithm for segmenting WBCs from microscopic blood images based on the thresholding segmentation technique and the authors compared their results with the most commonly used segmentation technique which is known as colour‐k‐means clustering. As the authors reported, their thresholding‐based proposed segmentation technique outperforms the colour‐k‐means clustering [21]. Continuously, in 2020, another CAD system for recognising the blast cells from bone marrow images in which the leukaemia can be identified was developed by Nikitaev et al To separate the nucleus of the cells from the input images, two segmentation techniques were used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhana et al proposed a new algorithm for segmenting WBCs from microscopic blood images based on the thresholding segmentation technique and the authors compared their results with the most commonly used segmentation technique which is known as colour‐k‐means clustering. As the authors reported, their thresholding‐based proposed segmentation technique outperforms the colour‐k‐means clustering [21]. Continuously, in 2020, another CAD system for recognising the blast cells from bone marrow images in which the leukaemia can be identified was developed by Nikitaev et al To separate the nucleus of the cells from the input images, two segmentation techniques were used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital image processing plays a significant role in various areas such as medical image processing [1], image inpainting [2], pattern recognition, biometrics, content-based image retrieval (CBIR), image compression, information hiding [3], and multimedia security [4]. The retrieval of similar images from a large range of images is becoming a serious challenge with the advent of digital communication technology and the growing use of the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…Beside content-based image retrieval (CBIR), digital image processing plays a vital role in numerous areas such as processing and analyzing medical image [1], image inpainting [2], pattern recognition [3], biometrics [4], multimedia security [5], and information hiding [6]. In the area of image processing and computer vision, CBIR has grown increasingly as an advanced research topic.…”
Section: Introductionmentioning
confidence: 99%